DETERMINATION OF THE SHEAR-STRENGTH REQUIREMENT FOR THE ADHESIVE USED BETWEEN CAVITY FILLING MATERIALS AND DENTIN - EKİCİ, BÜLENT (ELSEVIER SCI LTD, 1993)
A finite element technique is used to examine the stress distribution in a human first premolar with and without cavity preparation by using 2- and 3-dimensional models. The effects of different adhesive materials as cavity fillers on stress distribution are investigated. Since one of the most important factors affecting the success of a restoration process in clinical applications is the strength of the adhesive, the shear stresses obtained from numerical research are investigated in detail. Although in clinical applications the interfacial space between filling material and dentine is very important, it is assumed to be negligible here since it will not help in calculating the shear strength requirements of the adhesive. Therefore, one of the assumptions used throughout the analysis is that there are no interfacial spaces. In order to determine the effects of adhesive, all possible situations are included in the analyses. Different adhesives and different cavity filling materials are used in the model. In addition to these conditions, the effects of spring support conditions and temperature are also considered in the study.
Keywords: FIRST PREMOLAR; FEM ANALYSIS; DENTAL RESTORATION; ADHESIVES FOR TEETH; SHEAR STRENGTH OF DENTAL ADHESIVES; STRESS-ANALYSIS; TEETH